Análisis Del Mercado Laboral En Ecuador Durante La Pandemia De La Covid19 Período 2019-2020 - Belduma Belduma, Maribel Johanna (2023)
The present research work includes a detailed analysis of the labor market in Ecuador during the COVID-19 pandemic, in order to understand the main trends and challenges in this area. For the purpose of accomplishing this study, an exhaustive bibliographic review of the subject is carried out and the most relevant statistical data are thoroughly analyzed. The results of the analysis reveal that the COVID-19 pandemic has generated a considerable impact on the labor market worldwide, also affecting Ecuador significantly. The existing literature provides a detailed overview of the challenges and consequences that the country has faced in this context. The studies reviewed point to a direct correlation between the pandemic and a significant increase in unemployment in Ecuador. This increase especially affected informal workers and women. In addition, it is estimated that 48.6% of jobs in the country are informal, which has made difficult to implement social protection measures for workers. The discussion focuses on the need to implement labor policies target on mitigating the economic and social impacts of the pandemic. These measures seek not only to boost economic recovery, but also to improve job security and promote gender equity in the workplace. Finally, recommendations and proposals aimed at improving the country's labor situation are presented, such as the implementation of programs to improve the labor market. Finally, recommendations and proposals aimed at improving the labor situation in the country are presented, such as the implementation of public investment programs for employment generation, the promotion of teleworking and the training of workers to adapt to the new demands of the labor market.